A Study on Micro-Pore Characteristics of Clay Due to Freeze-Thaw and Compression by Mercury Intrusion Porosimetry - Wang, Shengfu; Yang, Ping; Dai, Daowen; Xue, Kaixi; Li, Dongwei (Frontiers in Earth Science, 2020)
Accurate quantification of soil micro-pore is important for understanding compression deformation and thaw settlement of fine-grained soils, including clay. This study presents mercury intrusion porosimetry (MIP) data on the four types of soil samples before and after freeze-thaw and compression under four different cold-end temperatures. Undisturbed clay specimens were subject to one-directional freeze-thaw in a closed system under different freezing temperatures. The frozen-thawed specimens were divided into three layers and averaged along the height direction for a consolidation test. The mercury intrusion test data were analyzed, and three typical micro-pore parameters including (1) total pore volume, (2) median pore size, and (3) average pore size were selected to quantitatively describe the variation of soil micro-pores before and after freeze-thaw and consolidation. Close correlations were observed between the variation of micro-pore parameters and variation of compression index, pore ratio, water content, and density. This study demonstrates that compared with traditional test methods, MIP can be advantageous in revealing the internal micro-pore change of soil due to freeze-thaw and compression both quantitatively and nondestructively.